The Influence of Social-Emotional Learning (SEL) in Understanding the Concept of Digital Citizenship - Fajar Setiawan; Bagus Nurul Iman; Arya Setya Nugroho; Muhammad Fazli Taib Bin Saearani (Profesi Pendidikan Dasar, 2026)
The massive digital transformation in the world of education requires teachers to be prepared as role models and character builders for the digital native generation. However, the digital literacy approach, which has so far focused on technical and instrumental aspects, is considered insufficient to shape responsible digital citizens. This study aims to analyze the influence of Social-Emotional Learning (SEL) on the understanding of the concept of Digital Citizenship among students of the Teacher Professional Education (PPG) Program in Elementary School Teacher Education (PGSD). The research method used a correlational design with a sample of 200 PPG PGSD students selected through proportional random sampling. Data were collected using a closed questionnaire. Data analysis used simple linear regression with a preliminary analysis prerequisite test. The results revealed a very significant influence between SEL and the understanding of the concept of Digital Citizenship (β = 0.995, p < 0.001) with a coefficient of determination R² = 0.989. The results of the normality and heteroscedasticity tests showed that the data were normally distributed and indicated heteroscedasticity. The implication of this study is that the development of SEL competencies in the teacher education curriculum is an imperative strategy for shaping prospective teachers who are not only digitally skilled but also socially and emotionally mature in leading digital transformation in the educational environment.